Hukum Adat dan Kearifan Lokal Aceh: Implementasi Syara’ dalam Tatanan Kebudayaan Aceh - Lubis, Muhammad Ikhsan; Inayah, Asti; Harahap, Salman Paris; Pradana, Adhitia (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
Aceh is known for its culture, which is closely related to Islamic laws. Islamic law itself developed in Aceh since the beginning of the entry of Islam into the archipelago, which began with the kingdom of Samudera Pasai. Since then, Islamic law has become the basis for the norms and rules of law that apply to the land of Rencong, which ultimately affects the life of society in Aceh. This foundation has become the motto and philosophy of life of the Acehnese people in the westernmost province of Indonesia, namely “hadih madja, adat ngon syari'at lagee dzat ngon sifeut” which means that sharia law and adat are like substance and nature. The customs and culture of the Acehnese people are diverse and correspond to the ethnic sections of each region in Aceh. This diversity reflects the richness and ethnic diversity of the Acehnese population. Customary law, in line with the implementation of Islamic Law applied in Aceh, has transformed into a unifying and adhesive in the structure and parts of the life of the Acehnese community, which in turn can serve as capital in the development structure in Aceh. Therefore, the joints and values of Aceh's customs and culture must be preserved, empowered, and cared for in the frame of unity and unity of social life towards the end of Aceh's special autonomy in 2027. This study discusses the perspective and role of customary law in Aceh, the definition of adat and customary law in terms of terminology, and the history of the application of adat and customary law in Aceh.